Mapping agricultural trade within the ECOWAS: Structure and flow of agricultural products, barriers to trade, financing gaps and policy options. A research project in cooperation with GIZ on behalf of BMZ - Olayinka Idowu Kareem; Christine Wieck (Universität Hohenheim, Institut für Agrarpolitik und Landwirtschaftliche Marktlehre, 2021)
This study reviews the structure and flow of formal and informal agri-food trade within ECOWAS and evaluate the trade barriers, financial and quality infrastructure gaps. A mixed-method approach - qualitative and quantitative methods - is adopted which comprises an extensive literature review, analysis of available statistical data on formal and informal trade and trade barriers, a field survey, expert interviews and workshops. The intra-ECOWAS agri-food trade is still at the low level with most of the traded agri-food commodities largely without value addition and characterised by inadequate diversification of the export base. A preponderance of informal agri-food trade along both the formal and informal trade corridors are detected. Livestock, oilseeds, cottonseed, nuts, cocoa beans, cereal, cassava, fisheries, fruits and vegetables were the most traded agri-food commodities, which were not given any concession of passage or facilitated across the borders despite the perishability of the commodities. Agri-food trade flows in the ECOWAS are largely hampered by the heterogeneous trade policy measures across the Member states. This is often a barrier to trade and tend to increase trade costs and commodities prices, thereby constraining the regional trade benefits to the people while also making the trading countries uncompetitive. Women agri-food traders were often exploited and harassed by the different borders' officials. More so, the low intra-ECOWAS trade in agricultural and food products is due to the low production capacities, which among others are due to the inadequate finance, poor quality infrastructure - soft (trained inspectors, customs procedures digitalisation, certification, etc) and hard (metrology facilities, roads, ports' facilities, testing and inspection laboratories, etc.). Agricultural trade finance has been identified as one of the key challenges inhibiting trade in agricultural commodities in this subregion. Strategic policy options to promote agri-food trade within ECOWAS are provided.
urn:nbn:de:bsz:100-opus-19876
Keywords: 380